Characterization of Thai Silk Fibroin Based Electrospun Nanofibrous Scaffolds for Articular Cartilage Cell Culture - Sathit Banthuek (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The main objective of this study has been to fabricate the Thai silk fibroin based electrospun nanofibrous scaffolds for articular cartilage cell culture. In this research contribution, electrospinning was used to fabricate silk fibroin (SF) nanofibers from cocoons of indigenous Thai Bombyx mori silkworms (Nangnoi Srisaket-I). The effects of SF concentration (i.e., 20–50% (w/v) in 98% formic acid) and applied voltage (i.e., 15, 20 and 25 kV) on morphology and diameter size of the electrospun SF nanofibrous scaffolds were investigated by Scanning Electron Microscopy (SEM). To confirm the composition structure of silk fibroin, the chemical structure of silk fibroin nanofibers was investigated by Fourier Transform Infra Red Spectroscopy, (FTIR) compare with degummed silk fiberse. The average diameter of the resulting of electrospun SF nanofibrous scaffolds was found to increase with the increase in the solution concentration. Furthermore, the fiber diameter has also been considered as the main factor to influence the mechanical properties of silk fibroin nanofibrous scaffold. These characteristic could provide the utility data of Thai silk fibroin nanofiners for tissue engineering applications. In addition, Electrospinning technique could produce nanofibers in the range of diameter from 100–300 nm. which have nearby diameter size of collagen fibers in articular cartilage extracellular matrix. For Biocompatibily, silk nanofibrous scaffolds showed non-toxicity toward PBMC cell and chondrocyte cell line, sw1353. This contribution provided some characteristic of Thai silk fibroin nanofibers that could be apply for biomaterials and tissue engineering applications.